A revision of the bee genus Ancyloscelis (Hymenoptera: Apidae) in Argentina - Schaller, A.; Roig-Alsina, A. (Zootaxa, 2021)
A revision of the emphorine bee genus Ancyloscelis in Argentina is presented. The genus extends from the United States to the center of Argentina, but the maximum diversity of morphological structures is found among South American species. Its species form two distinctive groups regarding their mouthparts: one of them with hooked setae on the proboscis, and the other one with simple or plumose setae on the proboscis. To the first group belong in Argentina, A. bonariensis Brèthes, A. halictoides (Holmberg), A. mesopotamica (Holmberg), and the new species A. holmergi. To the second group belong in Argentina A. apiformis (Fabricius), A. romeroi (Holmberg), A. saltensis Rodríguez & Roig-Alsina, and A. nigricornis Rodríguez & Roig-Alsina. Lectotype designations are made for Leptergatis bonariensis Brèthes and Leptergatis mesopotamica Holmberg. Ancyloscelis turmalis Vachal is a junior new synonym of Ancyloscelis mesopotamica. The synonymy of Ancyloscelis gigas Friese as junior synonym of Ancyloscelis halictoides is confirmed. Descriptions, illustrations, and a key to the species are provided.